2010
DOI: 10.1007/s00586-010-1593-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the psoas muscle and lumbar plexus with respect to the surgical approach for lateral transpsoas interbody fusion

Abstract: Lateral transpsoas interbody fusion (LTIF) is a minimally invasive technique that permits interbody fusion utilizing cages placed via a direct lateral retroperitoneal approach. We sought to describe the locations of relevant neurovascular structures based on MRI with respect to this novel surgical approach. We retrospectively reviewed consecutive lumbosacral spine MRI scans in 43 skeletally mature adults. MRI scans were independently reviewed by two readers to identify the location of the psoas muscle, lumbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 9 publications
0
62
0
5
Order By: Relevance
“…2 shows, the rate of anterior groin/thigh pain drops significantly over the follow-up time. This might be attributed to a transient irritation of the genitofemoral nerve damage which crosses at L2-3 [5,9]. Surgeons have theorized that this may be related to direct cutaneous nerve neuropraxia or an indirect mechanism via a psoas muscle inflammatory response due to mechanical dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 shows, the rate of anterior groin/thigh pain drops significantly over the follow-up time. This might be attributed to a transient irritation of the genitofemoral nerve damage which crosses at L2-3 [5,9]. Surgeons have theorized that this may be related to direct cutaneous nerve neuropraxia or an indirect mechanism via a psoas muscle inflammatory response due to mechanical dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Although Park et al [6] showed that the lumbar plexus with hip flexion travels more anterior (non-significant) the advantages of a relaxed and therefore easier-to-dissect muscle seem to out weigh the change in position of the nerves. The deciding factor for the side of the approach should be the anatomy of the psoas muscle relative to the approached disc level as described by Kepler [9]. Other critical factors are the relationship of the pelvis to L4-5 level, the coronal angulation of the approached disc space and the side of the concavity of the curve.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative magnetic resonance imaging can be helpful to identify the position of the psoas and the approximate locations of the lumbar plexus and vascular structures, although the operative position (lateral decubitus with hips and knees flexed) is quite different than the supine position [1,[4][5][6][7].…”
Section: Techniquementioning
confidence: 99%
“…Furthermore, biomechanical studies show that LLIF implants provide a greater reduction in range of motion during flexion, extension, lateral bending, and axial rotation when compared to those of anterior lumbar interbody fusion and TLIF implants [15,16]. The most common complication is anterior thigh pain and numbness, which result from irritating the psoas muscle or transient irritation of the genitofemoral nerve [1,4,5,8]. Pumberger et al [17] examined 181 patients at our institute.…”
mentioning
confidence: 99%
“…In 2011, two articles [2,3] provided important knowledge on the regional neural and vascular anatomy related to the transpsoas approach, providing quantitative and qualitative data to better understand and control the risk of injury to the lumbar plexus. In 2012, a retrospective study [4] on the neurological safety of the procedure (one of the hottest topics related to transpsoas surgery) was published in the Journal.…”
mentioning
confidence: 99%